KEDUDUKAN HUKUM KOMISI PENGAWAS PERSAINGAN USAHA MELAKSANAKAN WEWENANG PENEGAKAN HUKUM PERSAINGAN USAHA - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The main discussion of this research is concerning the position of KPPU in conducting the task and obligation to overcome and figure out suspect of monopoly practice and unfairly business competition which violate Act Number 5 of 1999. Research results show that in enforcing business competition law and resolving allegation of monopolistic business practice, the KPPU assumes the role as a state auxiliary organ that is independent from government intervention. In practice, the KPPU is a quasi judicial entity oecause it has the authority to similar to a court S, inter alia the authority to issue decrees and render judgments.